2012
DOI: 10.7314/apjcp.2012.13.8.3863
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial D-Loop Polymorphism and Microsatellite Instability in Prostate Cancer and Benign Hyperplasia Patients

Abstract: In this study mitochondrial D-Loop variations in Iranian prostate cancer and benign prostatic hyperplasia (BPH) patients were investigated. Tumour samples and corresponding non-cancerous prostate tissue from 40 prostate cancer patients and 40 age-matched BPH patients were collected. The entire mtD-loop region (16024-576) was amplified using the PCR method and products were gel-purified and subjected to direct nucleotide sequencing. A total of 129 variations were found, the most frequent being 263AgG and 310TgC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…However, the C16069T polymorphism has been reported in prostate cancer [25], pancreatic cancer [26], endometrial cancer [27], breast cancer [28,29], repeated pregnancy loss [30] and age-related macular degeneration [31]. This result supports our hypothesis, which shows the potential of specific mitochondrial 16069 polymorphism involvement in carcinogenesis.…”
Section: Discussionsupporting
confidence: 86%
“…However, the C16069T polymorphism has been reported in prostate cancer [25], pancreatic cancer [26], endometrial cancer [27], breast cancer [28,29], repeated pregnancy loss [30] and age-related macular degeneration [31]. This result supports our hypothesis, which shows the potential of specific mitochondrial 16069 polymorphism involvement in carcinogenesis.…”
Section: Discussionsupporting
confidence: 86%
“…For this reason, in the literature, it is assumed that a mutation in the D-loop can modulate the mtDNA copy number, subsequent OXPHOS dysfunction, and increased ROS [11]. The CR of the mtDNA is a hotspot for both germline and somatic mtDNA alterations in various types of tumors such as head and neck, colorectal, lung, bladder, uterine cervix and breast cancers as well as melanoma [12][13][14]. Moreover, several studies have reported that mtDNA polymorphisms and mitochondrial haplogroups have either a predisposing or protective role in various cancer types [15].…”
Section: Introductionmentioning
confidence: 99%
“…The CR region of the mtDNA is the hotspot for both germline and somatic mtDNA alterations. In addition, the most frequent DNA alterations in the mitochondrial genome were reported in the hypervariable segment-1 (HSV1, np 16204-16383) and -2 (np 57-373) of the CR, which were mostly located in the D-loop, at various types of tumors such as head and neck, colorectal, lung, bladder, melanoma, uterine cervix and breast cancer (Ashtiani et al, 2012;Cai et al, 2011;Zhang et al, 2015). Further associations were also established between single nucleotide polymorphisms (SNPs) of the CR and various complex diseases such as; metabolic syndrome, type II diabetes mellitus (DM), neurodegenerative diseases and aging in literature (Ghezzi et al, 2005;Guney et al, 2014;Mueller et al, 2011;Tipirisetti et al, 2014;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%